Superhydrophilic/superhydrophobic surfaces fabricated by spark-coating - T. Kumpika (2018)
Copyright © 2018 John Wiley & Sons, Ltd. In this study, the authors researched the preparations of superhydrophilic/superhydrophobic surfaces on commercial cup stock polyethylene coated papers by using sparked aluminum nanoparticles deposited on substrates through a sparking process. In this stage, the surface was porous and showed superhydrophilic properties. The samples were then annealed in air at various temperatures and some transformed to superhydrophobicity. It is well known that a suitable roughness in combination with low surface energy has been required to obtain superhydrophobic surfaces. Therefore, it is believed that during annealing process, when polyethylene is diffused from the substrate through the nanoparticle films and the superhydrophobic characteristics were created. The scanning electron microscope images showed that the film surfaces had a fluffy structure for both the as-deposited and the annealed samples. However, the atomic force microscopy phase images showed completely different surface properties. Moreover, the X-ray photoelectron spectroscopy spectra showed different surface chemical compositions. The experimental results revealed that the working temperature to produce superhydrophobic surfaces depended on the sparked film thickness. Furthermore, in order to prove the assumption explained above, glass and poly (methyl methacrylate) were also used as substrates.